The Relationship Between Corporate Social Responsibility, Brand Image, and Customer Loyalty: A Case Study of Le Minerale Consumers - Laksmono, Rendro; Purnama, Kusna Djati (International Journal of Business, Law, and Education, 2024)
This study investigates the relationships between Corporate Social Responsibility (CSR), Brand Image, and Customer Loyalty among consumers of Le Minerale, a prominent bottled water brand. Using a sample of 500 respondents, we employed regression analysis to test four hypotheses. The findings reveal that CSR significantly enhances both Brand Image and Customer Loyalty. Moreover, Brand Image mediates the relationship between CSR and Customer Loyalty, indicating that the positive impact of CSR on customer loyalty is maximized through a strong brand image. These results underscore the strategic importance of CSR in brand management and its role in fostering customer loyalty. Companies that effectively integrate and communicate their CSR initiatives can create a favorable brand image, thereby enhancing customer loyalty. The study contributes to the literature by providing empirical evidence of the mediating role of Brand Image in the CSR-customer loyalty relationship and offers practical insights for companies aiming to leverage CSR for competitive advantage.